Mohan Thapliyal ki sampoorn khahaniya - Gerola, Geeta (ed.) (Dehradun Samay sakshay, 2018)
Mohan Thapliyal is the famous story writer. His stories are being discussed in Hindi literature. Mohan Thapliyal is known as a struggling and bizarre writer in ordinary life. Having done four or five jobs, resigned from the government job in 1973 and joined the Jawaharlal Nehru University, Delhi. Where studied German language. He has connected with Lucknow's Literature House for some time. After that Journalism with daily Amrit Prabhat from 1979 to 1990. also translated the poems and stories of German poet Bertolt Brecht from the original German to Hindi and Albert Einstein's biography. Which was published in the form of a book. Your two story collections have previously been published in 1983 and 2000. Mohan Thapliyal was born on 14 October 1942 in Dayarabagh of Tehri district.
Keywords: Fiction; Mohan Thapliyal